PENGEMBANGAN EVALUASI PEMBELAJARAN EKONOMI BERBASIS WEBSITE PADA SISWA KELAS XI DI SMAN 1 SAMBAS - Zainal Zainal; Nuraini Asriati; Husni Syahrudin (ICoTE Proceedings, 2019)
The development of web-based economic evaluation is aimed at facilitating the real situation in the field. The actual situation is the existence of technology that has been owned by students as a whole as smartphones and computers. This study aims to provide an effective media for assessment of learning. This study was conducted at Sambas Secondary School 1. This research and development, ie, examines without testing where the purpose of this development research is to find potential. The method used to find potential research and development (Research and Development) is the ADDIE method